Communication and Bioethics at the End of Life - Roscoe, Lori A.; Schenck, David P. (Springer, 2017)
This book is a collection of real-life cases exploring the complex range of issues inherent in contemporary end-of-life medical care. It is intended for physicians, medical students, residents, ethics committee members, social workers, chaplains, nurses, bioethicists, researchers, and scholars who confront ethical issues with patients and families at the end of life, and who are committed to an understanding of the ways in which things can go wrong in efforts to improve our American way of dying. Most Americans die in institutional settings, primarily hospitals, which involve a challenging set of circumstances to be considered in helping patients die well. Media saturation, concerns for privacy, institutional norms, cultural diversity, politics, technology, and advances in medical care all complicate the decision-making, communication, and ethical analysis that are part of the dying process. More individual concerns, including family dynamics, patient preferences, spirituality, and insufficient advance care planning, also confound solutions that satisfy all stakeholders. End-of-life care is a controversial matter. The classic cases of In re Quinlan (1976) and Cruzan v. Director (1990) established the right of patients or their surrogates to refuse life-sustaining treatment, but the more recent case of Terri Schiavo (Caplan et al. 2006) demonstrated how difficult it can be to exercise this right in the face of family conflict, media coverage, and political chicanery. The same year that Schiavo lapsed into a persistent vegetative state, retired pathologist Jack Kevorkian euthanized his first patient in Oakland County Michigan (Roscoe et al. 2000). Kevorkian went on to assist the deaths of over 100 people illegally between 1990 and 1997 until his arrest, conviction, prison sentence, and eventual death. Today, 20% of Americans live in a state where physician-assisted suicide (which is a highly regulated version of what Kevorkian practiced) is legal; California is the most populous U.S. state to legalize this practice, and one of the most recent. Since Oregon passed itsDeath with Dignity statute in 1997, 1,545 terminally ill people have had lethal prescriptions written for them, and 991 have died from ingesting these medications (Oregon Public Health Division 2015). That same year, the U.S. Supreme Court heard two cases—Vacco v. Quill (1997) and Washington v. Glucksberg (1997)—and found no constitutionally protected right to die; the ruling was predicated in part by the hope expressed by Justice Sandra Day O’Connor that all Americans would be able to access high-quality end-of-life care.
Real Cases, Real Dilemmas